2003
DOI: 10.1046/j.1365-2230.2003.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of 124 Indian patients with lichen planus pigmentosus

Abstract: Lichen planus pigmentosus is a fairly common disorder of pigmentation in Indians, but reports comprising a sizeable number of patients are lacking in the literature. We now describe the clinical and epidemiological features and histopathological findings for 124 lichen planus pigmentosus patients. A retrospective analysis of medical records of patients attending our centre during the past 12 years was undertaken. Of the 124 patients (56 male, 68 female), the majority (48.4%) had the disease for 6 months to 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
271
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(292 citation statements)
references
References 10 publications
13
271
2
6
Order By: Relevance
“…Kanwar et al suggested that mustard oil, amla oil, henna and hair dye could be the precipitating factors in predisposed individuals [2]. These factors could not be identified in any of our patients.…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…Kanwar et al suggested that mustard oil, amla oil, henna and hair dye could be the precipitating factors in predisposed individuals [2]. These factors could not be identified in any of our patients.…”
contrasting
confidence: 55%
“…Palms, soles and nails are not affected. Although lesions are generally asymptomatic, mild pruritus and burning sensations are present in about one-third of patients [2]. In our pediatric series, the trunck was the most common site of lesions, itching was present in only one patient.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Besides extensive, perifollicular, linear or zosteriform distribution, lichen planus pigmentosus may follow the lines of Blaschko (Figure 10) or the course of the saphenous varicose veins on the legs [48,49]. Sites of predilection include intertriginous regions or the fl exures of the limbs [49,50].…”
Section: Lichen Planus Pigmentosusmentioning
confidence: 99%